PEMBELAJARAN EKSTRAKULIKULER SENI LUKIS KACA DI SMP NEGERI 3 SUKASADA - Suryawan, I Gde (Institut Seni Indoensia Surakarta, 2018)
Glass painting art as a â€œKosa Rupa Baliâ€ wealth especially Buleleng was very important to keep, one of them was in education. Because of that, it must be trained and directed for skill development through glass painting art extracuricular in many level, in this research focus on junior high scool especially at SMP N 3 Sukasada. The problem, that would be analyzed in this research are: (1) How are the glass painting art extracuricular learning process at SMP N 3 Sukasada. (2) How is the result of glass painting art extracurricularat SMP N 3 Sukasada. (3) What are the factor that affect the glass painting art extracuricular at SMP N 3 Sukasada. The research method that used was qualitative. The location that was choose for this research was SMP N 3 Sukasada. The technique that was used for collecting the data included: observation, interview, and documentation. The data was analysed by descriptive.Â Keywords: Learning, Ekstracuricular, Glass Painting